Preparation method of ball cactus-shaped sodium ion battery positive electrode material
Through wet grinding, spray drying and one-step calcination treatment, a sodium ferrophosphate phosphate positive electrode material with a surface coated with nitrogen-doped carbon material was formed, which solved the problems of poor conductivity, low capacity, poor low temperature performance, poor circulation performance and poor high rate performance, and significantly improved the overall performance of the battery.
Patent Information
- Application Number
- CN202510173843.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-18
AI Technical Summary
The existing sodium ferric pyrophosphate positive electrode materials have poor conductivity, low capacity, poor low temperature performance, poor circulation performance and poor high rate performance.
Through wet grinding, spray drying and one-step calcination treatment, carbon nanotubes and carbides of gelatin form a burr-like structure of nitrogen-doped material on the surface of the sodium ferropyrophosphate positive electrode material, and a cactus-like surface is prepared to obtain a sodium ferropyrophosphate positive electrode material with a cactus spherical surface coated with nitrogen-doped carbon material.
It significantly improves the conductivity, capacity, low temperature performance, cycle performance and high rate performance of the positive electrode material, and enhances the charging and discharging performance and service life of the battery.
Smart Images

Figure CN119660724A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium ion positive electrode materials, and in particular to a method for preparing a cactus-shaped sodium ion battery positive electrode material. Background Art
[0002] Based on years of technological development and optimization, lithium-ion batteries have become the representative of secondary batteries with the best comprehensive performance since their commercialization in the 1990s, with mature battery technology routes. However, due to the continuous development of the new energy industry and the abundance limitation of lithium in the earth's crust, lithium-ion batteries may gradually find it difficult to support the current growing demand for energy storage. The working principle of sodium-ion batteries is similar to that of lithium-ion batteries, but the reserves of sodium salt resources are more abundant and the mining is simpler, which has broad prospects for large-scale applications in the field of energy storage.
[0003] Sodium ion batteries include positive electrodes, negative electrodes, electrolytes, separators and accessories. Among them, the performance of positive electrode materials and negative electrode materials plays a decisive role in the overall performance of sodium ion batteries, especially positive electrode materials. Sodium iron phosphate, as a sodium ion positive electrode material, has the advantages of low cost, environmental friendliness and stable structure.
[0004] However, the existing sodium iron phosphate pyrophosphate positive electrode material still has the following disadvantages: First, poor conductivity: Sodium iron pyrophosphate generally exhibits low electronic conductivity and sodium ion diffusion rate, which will lead to increased internal resistance of the battery and intensified polarization during the charge and discharge process, affecting the overall efficiency and power output of the battery.
[0005] Second, the capacity is low: Although sodium ferric pyrophosphate has a certain theoretical specific capacity, its actual available capacity is often low.
[0006] Third, the low-temperature performance is poor: Under low-temperature conditions, the ion diffusion rate of sodium iron pyrophosphate is significantly reduced, and the electronic conductivity is also affected, resulting in an increase in the internal resistance of the battery and an increase in the voltage drop, which in turn affects the battery's charge and discharge performance.
[0007] Fourth, the cycle performance is poor: after long-term cyclic use, the capacity decay is accelerated, which will affect the service life of the battery.
[0008] Fifth, high-rate performance is poor: Due to insufficient electronic conductivity and sodium ion diffusivity, existing positive electrode materials perform poorly at high-rate charge and discharge.
[0009] Therefore, it is necessary to effectively improve the conductivity, capacity, low temperature performance, cycle performance and high rate performance of sodium iron pyrophosphate positive electrode materials. Summary of the invention
[0010] 1. Technical issues to be resolved In view of the above technical problems, the present invention provides a method for preparing a cactus-shaped sodium ion battery positive electrode material, which can effectively improve the conductivity, capacity, low temperature performance, cycle performance and high rate performance of the sodium iron pyrophosphate positive electrode material.
[0011] (II) Technical solution In order to achieve the above object, the main technical solutions adopted by the present invention include: A method for preparing a cactus-shaped sodium ion battery positive electrode material comprises the following steps: S1: wet-grinding a mixture of a sodium source, an iron source, a phosphorus source, gelatin and carbon nanotubes to obtain a slurry; S2: spray drying the slurry to obtain a precursor powder; S3: The precursor powder obtained in step S2 is subjected to a one-step calcination treatment in an oxygen-free environment to obtain a sodium iron phosphate pyrophosphate positive electrode material having a cactus-shaped surface coated with nitrogen-doped carbon material.
[0012] The method for preparing the cactus-shaped sodium ion battery positive electrode material as described above, preferably, in step S1, the molar ratio of the sodium element, the iron element and the phosphorus element in the sodium source, the iron source and the phosphorus source is 4:(2.8-3):4; The carbon element in the gelatin accounts for 1-5% of the total mass of the mixture of the sodium source, the iron source, the phosphorus source, the gelatin and the carbon nanotubes; Carbon nanotubes make up 5-15% of the gelatin mass.
[0013] The method for preparing the cactus-shaped sodium ion battery positive electrode material as described above, preferably, in step S1, the sodium source is one or more of sodium carbonate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium oxalate and sodium pyrophosphate; The iron source is one or more of ferrous phosphate, ferrous citrate, ferrous oxalate, ferrous acetylacetonate, ferrous nitrate, ferric chloride and ferrous sulfate; The phosphorus source is one or more of phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ferric phosphate, ferric pyrophosphate and sodium dihydrogen phosphate.
[0014] In the method for preparing the cactus-shaped sodium ion battery positive electrode material as described above, preferably, in step S1, after mixing the sodium source, the iron source, the phosphorus source, the gelatin and the carbon nanotubes, water is added to obtain a mixed material, and then wet grinding is performed; Among them, the rotation speed of wet grinding is 2000-3000r / min, the flow rate of the mixed material through the wet grinding equipment during wet grinding is 50-100L / h, the duration of wet grinding is 0.5-10h, the particle size of the grinding medium used in wet grinding is 0.03-0.3mm, and the grinding medium occupies 70-85% of the volume of the grinding chamber.
[0015] In the method for preparing the cactus-shaped sodium-ion battery positive electrode material as described above, preferably, in the slurry obtained in step S1, the solid content is 15-40wt%, and the particle size of the solid particles is 50-200nm.
[0016] In the method for preparing the cactus-shaped sodium ion battery positive electrode material as described above, preferably, in step S2, the feed rate of spray drying is 60-90 mL / min, the pressure of the spray gun is 0.2-0.4 MPa, the feed temperature is 190-240° C., and the discharge temperature is 80-130° C.
[0017] The method for preparing the cactus-shaped sodium ion battery positive electrode material as described above, preferably, in step S3, the precursor powder obtained in step S2 is subjected to a one-step calcination treatment in a mixed atmosphere of nitrogen and ammonia to obtain a cactus-shaped sodium iron phosphate pyrophosphate positive electrode material with a nitrogen-doped carbon material coated on the surface; In the mixed atmosphere, ammonia accounts for 10-20% by volume.
[0018] In the method for preparing the cactus-shaped sodium-ion battery positive electrode material as described above, preferably, in step S3, the precursor powder is heated to 400-600° C. at a heating rate of 2-8° C. / min, calcined for 5-16 h, and then cooled.
[0019] In the method for preparing the cactus-shaped sodium-ion battery positive electrode material as described above, preferably, in step S3, the cooling time is 10-60 min.
[0020] In the above-mentioned method for preparing the cactus-shaped sodium ion battery positive electrode material, preferably, in step S3, the structure formula of the cactus-shaped sodium iron phosphate pyrophosphate positive electrode material coated with nitrogen-doped carbon material is Na4Fe x (PO4)2P2O7@CN, 2.8<x≤3.
[0021] (III) Beneficial effects The present invention uses wet grinding, spray drying and one-step calcination treatment to make the carbon nanotubes and gelatin carbides form a nitrogen-doped material with a burr-like structure on the surface of the sodium ferric phosphate pyrophosphate positive electrode material, thereby obtaining the sodium ferric phosphate pyrophosphate positive electrode material with a cactus-shaped surface coated with nitrogen-doped carbon material.
[0022] The functions of carbon nanotubes are as follows: First, carbon nanotubes help to build a uniform and efficient conductive network, significantly improve the electron conductivity of the positive electrode material, reduce internal resistance, and enhance the charge and discharge performance of the battery. Second, carbon nanotubes are one of the key factors in forming a burr-like structure. The burr-like structure helps to build cactus-shaped particles, which can increase the specific surface area and the number of active sites of the material, and further enhance the electrochemical reaction activity of the positive electrode material. Third, the presence of carbon nanotubes can also achieve a balance between the density and porosity of the positive electrode material, which not only ensures high energy density, but also facilitates the penetration of the electrolyte and the electrochemical reaction.
[0023] Gelatin is rich in carbon and nitrogen, which is the key to the formation of nitrogen-doped carbon materials. The radius of carbon atoms is similar to that of nitrogen atoms. Nitrogen doping can change the atomic and electronic structure of the carbon layer matrix, increase the conductivity of the positive electrode material, and alleviate the lattice distortion of the composite material, improve the wettability of sodium iron pyrophosphate and the electrolyte, and further improve its conductivity. In addition, gelatin has excellent adhesion and stability, which can effectively improve the agglomeration of precursor powders and ensure uniform dispersion of materials.
[0024] One-step calcination treatment is also one of the key steps to form the cactus-like morphology. The cactus-like morphology can significantly increase the specific surface area, interlayer spacing and porosity of the positive electrode material, and increase the contact area between the positive electrode material and the electrolyte.
[0025] In summary, nitrogen-doped carbon materials and the efficient conductive network they form can significantly improve the electron conduction capacity of positive electrode materials and enhance conductivity. Based on the effects of efficient conductive networks and nitrogen doping, as well as the large specific surface area, rich pore structure and large interlayer spacing of cactus-shaped particles, the contact area between the positive electrode material and the electrolyte is increased, the capacity of the positive electrode material is improved, and sodium ions can diffuse rapidly under low temperature conditions, thereby improving the low temperature performance of the positive electrode material, while also improving the cycle performance and high rate performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM image of the sodium iron phosphate pyrophosphate positive electrode material with a cactus-shaped surface coated with nitrogen-doped carbon material prepared in Example 1; Figure 2 This is a SEM image of the sodium iron phosphate pyrophosphate positive electrode material with a cactus-shaped surface coated with nitrogen-doped carbon material prepared in Example 2; Figure 3 This is a SEM image of the sodium iron phosphate pyrophosphate positive electrode material prepared in Comparative Example 1; Figure 4 This is a first cycle charge and discharge curve of a battery composed of the sodium iron phosphate pyrophosphate positive electrode material prepared in Example 1. DETAILED DESCRIPTION
[0027] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0028] The present invention provides a method for preparing a cactus-shaped sodium ion battery positive electrode material, comprising the following steps: S1: wet-grinding a mixture of a sodium source, an iron source, a phosphorus source, gelatin and carbon nanotubes to obtain a slurry.
[0029] S2: spray drying the slurry to obtain a precursor powder.
[0030] S3: The precursor powder obtained in step S2 is subjected to a one-step calcination treatment in an oxygen-free environment to obtain a sodium iron phosphate pyrophosphate positive electrode material having a cactus-shaped surface coated with nitrogen-doped carbon material.
[0031] The present invention uses wet grinding, spray drying and one-step calcination to form a nitrogen-doped material with a burr-like structure on the surface of the sodium ferric phosphate pyrophosphate positive electrode material by using carbon nanotubes and gelatin carbides, thereby preparing a sodium ferric phosphate pyrophosphate positive electrode material with a cactus-shaped surface coated with nitrogen-doped carbon material. The special morphology of this cactus / burr-like structure can significantly increase the specific surface area and electrical transmission performance of the positive electrode material, and can take into account both high battery energy density and appropriate porosity, which helps the electrolyte to penetrate into the entire electrode.
[0032] In the present invention, the functions of carbon nanotubes (CNTs) include the following: First, carbon nanotubes help to build a uniform and efficient conductive network, significantly improving the electronic conductivity of the positive electrode material, reducing internal resistance, and enhancing the battery's charge and discharge performance.
[0033] Second, carbon nanotubes are one of the key factors in forming the burr-like structure. The burr-like structure helps to construct cactus-shaped particles, which can increase the specific surface area and the number of active sites of the material, and further enhance the electrochemical reaction activity of the positive electrode material.
[0034] Third, the presence of carbon nanotubes can also achieve a balance between the density and porosity of the positive electrode material, ensuring high energy density while facilitating the penetration of electrolyte and the progress of electrochemical reactions.
[0035] If only gelatin is used without adding carbon nanotubes, the burr-like structure cannot be formed and the cactus-like morphology cannot be formed on the surface of the positive electrode material, which leads to no obvious improvement in the various performances of the positive electrode material.
[0036] Gelatin is rich in carbon and nitrogen elements, and is the key to the formation of nitrogen-doped carbon materials. The radius of carbon atoms is similar to that of nitrogen atoms. Nitrogen doping can change the atomic and electronic structure of the carbon layer matrix, increase the conductivity of the positive electrode material, and alleviate the lattice distortion of the composite material. It improves the wettability of sodium iron pyrophosphate and the electrolyte, and further improves its conductivity.
[0037] In addition, gelatin has excellent adhesion and stability, and can effectively improve the agglomeration of precursor powder and ensure uniform dispersion of the material.
[0038] One-step calcination is also one of the key steps to form a cactus-like morphology. The cactus-like morphology can significantly increase the specific surface area, interlayer spacing and porosity of the positive electrode material, and increase the contact area between the positive electrode material and the electrolyte. If a two-step calcination treatment is used in step S3, the surface of the prepared positive electrode material cannot form a burr-like structure, and the surface of the positive electrode material cannot form a cactus-like morphology.
[0039] Preferably, in the above step S1, the molar ratio of sodium element, iron element and phosphorus element in the sodium source, iron source and phosphorus source is 4: (2.8-3): 4. The carbon element in gelatin accounts for 1-5% of the total mass of the mixture of the sodium source, iron source, phosphorus source, gelatin and carbon nanotubes, and the carbon nanotubes account for 5-15% of the mass of gelatin.
[0040] The sodium source can be one or more of sodium carbonate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium oxalate and sodium pyrophosphate; the iron source can be one or more of ferric phosphate, ferrous citrate, ferrous oxalate, ferrous acetylacetonate, ferric nitrate, ferric chloride and ferrous sulfate; the phosphorus source can be one or more of phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ferric phosphate, ferric pyrophosphate and sodium dihydrogen phosphate.
[0041] The specific operation of step S1 is as follows: after mixing the sodium source, the iron source, the phosphorus source, the gelatin and the carbon nanotubes, water is added to obtain a mixed material, and then wet grinding is performed. The rotation speed of the wet grinding is 2000-3000r / min, the flow rate of the mixed material passing through the wet grinding equipment during the wet grinding process is 50-100L / h, the wet grinding time is 0.5-10h, the particle size of the grinding medium used in the wet grinding is 0.03-0.3mm, and the grinding medium occupies 70-85% of the volume of the grinding chamber.
[0042] After step S1 is completed, the solid content of the obtained slurry is 15-40wt%, and the particle size of the solid particles in the slurry is 50-200nm.
[0043] Preferably, in the above step S2, the slurry can enter the spray drying chamber through a spray gun, the feed rate of the spray drying is 60-90 mL / min, the pressure of the injection gun is 0.2-0.4 MPa, the feed temperature is 190-240°C, and the discharge temperature is 80-130°C.
[0044] Preferably, in the above step S3, the precursor powder obtained in step S2 can be subjected to a one-step calcination treatment in a mixed atmosphere of nitrogen and ammonia to obtain a sodium iron phosphate pyrophosphate positive electrode material with a cactus-shaped surface coated with nitrogen-doped carbon material. In the mixed atmosphere, the volume proportion of ammonia can be 10-20%.
[0045] In the mixed atmosphere formed by nitrogen and ammonia, nitrogen can be used as a protective gas to prevent the oxidation of the particle material. Ammonia can provide active nitrogen during the calcination process, further improving the level of nitrogen doping on the basis of gelatin. A small amount of nitrogen doping can improve the electrochemical performance of the coating material on the surface of the positive electrode material. The specific principle is as follows: 1. Nitrogen doping can introduce electron donors and improve the electronic conductivity of carbon materials, because higher conductivity can bring better charge and discharge performance.
[0046] 2. Nitrogen doping can provide additional redox active sites, which helps to enhance the pseudocapacitive properties of the positive electrode material, thereby improving the capacity and rate performance of the positive electrode material.
[0047] 3. Nitrogen doping can change the surface chemical properties of carbon materials, making their surfaces more hydrophilic and conducive to the infiltration of electrolytes.
[0048] 4. Nitrogen doping can add more active sites, which can promote the adsorption and desorption of ions, thereby improving the capacity and cycle stability of the positive electrode material.
[0049] Further preferably, in step S3, the precursor powder can be heated to 400-600°C at a heating rate of 2-8°C / min, then calcined for 5-16h, and finally cooled rapidly to obtain a sodium iron phosphate pyrophosphate positive electrode material with a cactus-shaped surface coated with nitrogen-doped carbon material. The cooling time needs to be maintained at 10-60min. In addition to the above-mentioned one-step calcination, rapid cooling will also affect the morphology of the positive electrode material. Rapid cooling can cause the expanded positive electrode material to shrink rapidly. Under the combined effect of one-step calcination and rapid cooling, a positive electrode material with a cactus-shaped morphology is finally obtained.
[0050] In addition, the general structural formula of the sodium iron phosphate pyrophosphate positive electrode material with a cactus-shaped surface coated with nitrogen-doped carbon material prepared in step S3 can be expressed as Na4Fe x (PO4)2P2O7@CN, where 2.8<x≤3.
[0051] In summary, nitrogen-doped carbon materials and the efficient conductive network they form can significantly improve the electron conduction capacity of positive electrode materials and enhance conductivity. Based on the effects of efficient conductive networks and nitrogen doping, as well as the large specific surface area, rich pore structure and large interlayer spacing of cactus-shaped particles, the contact area between the positive electrode material and the electrolyte is increased, the capacity of the positive electrode material is improved, and sodium ions can diffuse rapidly under low temperature conditions, thereby improving the low-temperature performance of the positive electrode material, and at the same time, it can also improve the cycle performance and high-rate performance of the positive electrode material.
[0052] In order to further clarify the scheme of the present invention and its technical advancement, the following is a description in conjunction with specific embodiments and technical effects.
[0053] Example 1
[0054] This embodiment provides a method for preparing a cactus-shaped sodium ion battery positive electrode material, comprising the following steps: S1: Sodium carbonate, iron phosphate, sodium dihydrogen phosphate, gelatin and carbon nanotubes are mixed, water is added to obtain a mixed material, and then wet-grinding is performed to obtain a slurry with a solid content of 16 wt % and an average particle size of solid particles of 150 nm.
[0055] In step S1, sodium carbonate and sodium dihydrogen phosphate are sodium sources, ferric phosphate is iron source, sodium dihydrogen phosphate and ferric phosphate are phosphorus sources. The molar ratio of sodium element, iron element and phosphorus element in the sodium source, iron source and phosphorus source is 4:2.91:4. The carbon element in gelatin accounts for 4% of the total mass of the mixture of sodium source, iron source, phosphorus source, gelatin and carbon nanotubes, and carbon nanotubes account for 10% of the mass of gelatin. The rotation speed of wet grinding is 2500r / min, the flow rate of the mixed material through the wet grinding equipment during wet grinding is 80L / h, the duration of wet grinding is 5h, the particle size of the grinding medium used in wet grinding is 0.1mm, and the grinding medium accounts for 78% of the volume of the grinding chamber.
[0056] S2: The slurry was spray dried, the feed rate of the spray drying was 75 mL / min, the pressure of the spray gun was 0.3 MPa, the feed temperature was 230° C., and the discharge temperature was 110° C. to obtain a precursor powder.
[0057] S3: In a mixed atmosphere of nitrogen and ammonia, the precursor powder was heated to 500°C at a heating rate of 2°C / min, then calcined for 10 hours, and then cooled for 30 minutes to obtain a sodium iron phosphate pyrophosphate positive electrode material with a cactus-shaped surface coated with nitrogen-doped carbon material. The volume proportion of ammonia in the mixed atmosphere was 15%.
[0058] The structural formula of the sodium iron phosphate pyrophosphate positive electrode material with a cactus-shaped surface coated with nitrogen-doped carbon material prepared in this embodiment is Na4Fe 2.91 (PO4)2P2O7@CN.
[0059] Example 2
[0060] This embodiment provides a method for preparing a cactus-shaped sodium ion battery positive electrode material, comprising the following steps: S1: After mixing ferrous oxalate, sodium dihydrogen phosphate, gelatin and carbon nanotubes, water is added to obtain a mixed material, which is then wet-milled to obtain a slurry with a solid content of 15 wt % and an average particle size of solid particles of 50 nm.
[0061] In step S1, sodium dihydrogen phosphate is the sodium source and phosphorus source, and ferrous oxalate is the iron source. The molar ratio of sodium element, iron element and phosphorus element in the sodium source, iron source and phosphorus source is 4:3:4. The carbon element in gelatin accounts for 5% of the total mass of the mixture of sodium source, iron source, phosphorus source, gelatin and carbon nanotubes, and carbon nanotubes account for 5% of the mass of gelatin. The rotation speed of wet grinding is 2000r / min, the flow rate of the mixed material through the wet grinding equipment during wet grinding is 50L / h, the duration of wet grinding is 0.5h, the particle size of the grinding medium used in wet grinding is 0.03mm, and the grinding medium accounts for 85% of the volume of the grinding chamber.
[0062] S2: The slurry is spray dried, the feed rate of the spray drying is 60 mL / min, the pressure of the spray gun is 0.2 MPa, the feed temperature is 240° C., and the discharge temperature is 80° C. to obtain a precursor powder.
[0063] S3: In a mixed atmosphere of nitrogen and ammonia, the precursor powder was heated to 550°C at a heating rate of 5°C / min, then calcined for 8 hours, and then cooled for 20 minutes to obtain a sodium iron phosphate pyrophosphate positive electrode material with a cactus-shaped surface coated with nitrogen-doped carbon material. The volume proportion of ammonia in the mixed atmosphere was 10%.
[0064] The structural formula of the sodium iron phosphate pyrophosphate positive electrode material with a cactus-shaped surface coated with nitrogen-doped carbon material prepared in this embodiment is Na4Fe3(PO4)2P2O7@CN.
[0065] Example 3
[0066] This embodiment provides a method for preparing a cactus-shaped sodium ion battery positive electrode material, comprising the following steps: S1: After mixing ferrous citrate, ferric phosphate, sodium pyrophosphate, gelatin and carbon nanotubes, water is added to obtain a mixed material, which is then wet-milled to obtain a slurry with a solid content of 40 wt % and an average particle size of solid particles of 200 nm.
[0067] In step S1, sodium pyrophosphate is the sodium source, ferrous citrate and ferric phosphate are the iron sources, and ferric phosphate and sodium pyrophosphate are the phosphorus sources. The molar ratio of sodium element, iron element and phosphorus element in the sodium source, iron source and phosphorus source is 4:2.95:4. The carbon element in gelatin accounts for 1% of the total mass of the mixture of sodium source, iron source, phosphorus source, gelatin and carbon nanotubes, and carbon nanotubes account for 15% of the mass of gelatin. The rotation speed of wet grinding is 3000r / min, the flow rate of the mixed material through the wet grinding equipment during wet grinding is 100L / h, the duration of wet grinding is 10h, the particle size of the grinding medium used in wet grinding is 0.3mm, and the grinding medium accounts for 70% of the volume of the grinding chamber.
[0068] S2: The slurry was spray dried, the feed rate of the spray drying was 90 mL / min, the pressure of the spray gun was 0.4 MPa, the feed temperature was 190° C., and the discharge temperature was 130° C. to obtain a precursor powder.
[0069] S3: In a mixed atmosphere of nitrogen and ammonia, the precursor powder was heated to 600°C at a heating rate of 8°C / min, then calcined for 5h, and then cooled for 60min to obtain a sodium iron phosphate pyrophosphate positive electrode material with a cactus-shaped surface coated with nitrogen-doped carbon material. The volume proportion of ammonia in the mixed atmosphere was 20%.
[0070] The structural formula of the sodium iron phosphate pyrophosphate positive electrode material with a cactus-shaped surface coated with nitrogen-doped carbon material prepared in this embodiment is Na4Fe 2.95 (PO4)2P2O7@CN.
[0071] Example 4
[0072] This embodiment provides a method for preparing a cactus-shaped sodium ion battery positive electrode material, comprising the following steps: S1: Disodium hydrogen phosphate, ferrous acetylacetonate, phosphoric acid, gelatin and carbon nanotubes are mixed, water is added to obtain a mixed material, and then wet-grinding is performed to obtain a slurry with a solid content of 20 wt % and an average particle size of solid particles of 100 nm.
[0073] In step S1, disodium hydrogen phosphate is the sodium source, ferrous acetylacetonate is the iron source, and phosphoric acid is the phosphorus source. The molar ratio of sodium element, iron element and phosphorus element in the sodium source, iron source and phosphorus source is 4:2.8:4. The carbon element in gelatin accounts for 3.5% of the total mass of the mixture of sodium source, iron source, phosphorus source, gelatin and carbon nanotubes, and carbon nanotubes account for 8% of the mass of gelatin. The rotation speed of wet grinding is 2200r / min, and the flow rate of the mixed material through the wet grinding equipment during wet grinding is 60L / h. The duration of wet grinding is 4h, and the particle size of the grinding medium used in wet grinding is 0.15mm, and the grinding medium accounts for 81% of the volume of the grinding chamber.
[0074] S2: The slurry is spray dried, the feed rate of the spray drying is 60-90 mL / min, the pressure of the spray gun is 0.3 MPa, the feed temperature is 200° C., and the discharge temperature is 100° C. to obtain a precursor powder.
[0075] S3: In a mixed atmosphere of nitrogen and ammonia, the precursor powder was heated to 400°C at a heating rate of 3°C / min, then calcined for 16 hours, and then cooled for 10 minutes to obtain a sodium iron phosphate pyrophosphate positive electrode material with a cactus-shaped surface coated with nitrogen-doped carbon material. The volume proportion of ammonia in the mixed atmosphere was 18%.
[0076] The structural formula of the sodium iron phosphate pyrophosphate positive electrode material with a cactus-shaped surface coated with nitrogen-doped carbon material prepared in this embodiment is Na4Fe 2.8 (PO4)2P2O7@CN.
[0077] Example 5
[0078] This embodiment provides a method for preparing a cactus-shaped sodium-ion battery positive electrode material, which is different from Embodiment 1 in that sodium oxalate is used as a sodium source, ferric nitrate is used as an iron source, and ammonium monohydrogen phosphate is used as a phosphorus source.
[0079] Example 6
[0080] This embodiment provides a method for preparing a cactus-shaped sodium-ion battery positive electrode material, which is different from Embodiment 1 in that sodium carbonate is used as a sodium source, ferric chloride is used as an iron source, and diammonium phosphate is used as a phosphorus source.
[0081] Example 7
[0082] This embodiment provides a method for preparing a cactus-shaped sodium-ion battery positive electrode material, which is different from Embodiment 1 in that sodium oxalate is used as a sodium source, ferrous sulfate is used as an iron source, and ferric pyrophosphate is used as a phosphorus source.
[0083] Comparative Example 1 This comparative example provides a method for preparing a positive electrode material for a sodium ion battery. The difference from Example 2 is that the precursor powder is heated to 300°C at a heating rate of 2°C / min in a nitrogen atmosphere and calcined for 3 hours, then heated to 600°C at a heating rate of 2°C / min and calcined for 10 hours, and then cooled naturally.
[0084] Comparative Example 2 This comparative example provides a method for preparing a positive electrode material for a sodium ion battery, which is different from Example 2 in that the amount of carbon nanotubes added is 0.
[0085] Comparative Example 3 This comparative example provides a method for preparing a positive electrode material for a sodium ion battery, which differs from Example 2 in that gelatin is replaced by glucose.
[0086] The microscopic morphology of the sodium ion positive electrode materials prepared in Examples 1-7 and Comparative Examples 1-3 was recorded by electron microscope observation. Figure 1-2 As shown, the surface of the sodium ion battery positive electrode material prepared in Example 1-2 has a burr-like structure, presenting a cactus-like morphology. Similarly, the surface of the sodium ion battery positive electrode material of Example 3-7 also has a burr-like structure, presenting a cactus-like morphology.
[0087] like Figure 3 As shown, the sodium ion battery positive electrode material prepared in Comparative Example 1 is a spherical particle, and there is no burr-like structure on the surface, and it does not have a cactus-like morphology. Similarly, the sodium ion battery positive electrode materials of Comparative Examples 2-3 are also spherical particles, and there is no burr-like structure on the surface, and they do not present a cactus-like morphology.
[0088] Through the morphological comparison of the above-mentioned embodiments and comparative examples, it can be seen that the one-step calcination treatment is the key step in forming the cactus-like morphology, and the two-step calcination treatment method will directly lead to the inability to form the cactus-like morphological characteristics on the surface of the sodium ion positive electrode material. In addition, carbon nanotubes are also a key factor in the formation of burr-like structures and cactus-like morphologies on the surface of the sodium ion positive electrode material. Since glucose does not contain nitrogen, even in a mixed atmosphere of nitrogen and ammonia, the sodium ion positive electrode material of Comparative Example 3 is difficult to form a burr-like structure on the surface and cannot present a cactus-like morphology.
[0089] The sodium ion positive electrode material, carbon black conductive agent and polyvinylidene fluoride prepared in Examples 1-7 and Comparative Examples 1-3 were mixed in a mass ratio of 90:5:5 to obtain a homogenate, which was coated on an aluminum foil and dried in a vacuum drying oven at 110°C for 4 hours to obtain a positive electrode film. The positive electrode film was punched into a disc with a radius of 0.6 mm using a punching machine, a metal sodium sheet was used as a counter electrode, NaClO4 with a concentration of 1 mol / L was dissolved in a mixed solvent of ethylene carbonate (EC) and propylene carbonate (PC) with a volume ratio of 1:1, and 5% by volume of fluoroethylene carbonate (FEC) was added as an additive to obtain an electrolyte, the separator was glass fiber, and a CR2016 button battery was assembled in a glove box.
[0090] The electrochemical performance tests of the above button cells were carried out. Unless otherwise specified, all tests were carried out at room temperature. The details are as follows: Carry out constant current charge and discharge test at a current density of 0.1C (1C = 129mAh / g), record and calculate the discharge capacity during the first discharge process, the unit is mAh / g, calculate the ratio of the actual amount of electricity discharged during the first charge and discharge process to the amount of electricity input during charging, and obtain the first cycle coulomb efficiency, expressed as a percentage. Figure 4It can be seen that within the voltage range of 2-4 V, the first discharge capacity of the battery corresponding to Example 1 is 109 mAh / g, and the first cycle coulombic efficiency is 88.99%.
[0091] Continue to perform 100 complete charge and discharge cycles at a current density of 0.1C, record the discharge capacity for each cycle, and calculate the capacity retention rate after the 100th cycle, that is, the ratio of the discharge capacity at the 100th cycle to the initial discharge capacity, expressed as a percentage.
[0092] Increase the current density to 5C, perform a complete charge and discharge cycle on the battery, and record and calculate the discharge specific capacity during this discharge process in mAh / g.
[0093] After the battery is placed in a -20°C environment and stabilized for a period of time, a complete discharge cycle is performed at a current density of 0.1 C. The discharge capacity at this low temperature is recorded and compared with the discharge capacity measured at room temperature to calculate the low-temperature discharge capacity retention rate, expressed as a percentage.
[0094] In addition, the specific surface area of the positive electrode materials prepared in each embodiment and comparative example is calculated, and the unit is m 2 / g.
[0095] The above parameters are shown in Table 1.
[0096] Table 1 Electrochemical performance data of sodium ion batteries corresponding to Examples 1-7 and Comparative Examples 1-3
[0097] It can be seen from Table 1 that the first discharge capacity of the battery assembled from the positive electrode materials of Examples 1-7 at a current density of 0.1C is 102-109 mAh / g, which is significantly higher than that of Comparative Examples 1-3, indicating that the capacity and conductivity of the sodium iron phosphate pyrophosphate positive electrode material of the cactus-shaped surface coated with nitrogen-doped carbon material of the present invention are improved. The first cycle coulomb efficiency of the battery assembled from the positive electrode materials of Examples 1-7 at a current density of 0.1C basically reaches 90% or more, which is significantly higher than 80-85% of Comparative Examples 1-3, indicating that the sodium iron phosphate pyrophosphate positive electrode material of the cactus-shaped surface coated with nitrogen-doped carbon material of the present invention has good conductivity. The capacity retention rate of the battery assembled from the positive electrode materials of Examples 1-7 after 100 cycles at a current density of 0.1C is above 99%, which is higher than 82-90% of Comparative Examples 1-3, indicating that the cycle performance of the sodium iron phosphate pyrophosphate positive electrode material of the cactus-shaped surface coated with nitrogen-doped carbon material of the present invention is significantly improved. The first discharge capacity of the battery assembled from the positive electrode materials of Examples 1-7 at a current density of 5C can reach 80-87% of the first discharge capacity of the battery at 0.1C, while Comparative Examples 1-3 can maintain at most around 72%, indicating that the high-rate performance of the sodium iron phosphate pyrophosphate positive electrode material with a cactus-shaped surface coated with nitrogen-doped carbon material of the present invention is good. The battery assembled from the positive electrode materials of Examples 1-7 can maintain a low-temperature discharge capacity retention rate of around 81-86% at -20°C and a current density of 0.1C compared to room temperature, while Comparative Examples 1-3 can only maintain 74% and below, indicating that the low-temperature performance of the sodium iron phosphate pyrophosphate positive electrode material with a cactus-shaped surface coated with nitrogen-doped carbon material of the present invention is improved.
[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a cactus-shaped sodium ion battery positive electrode material, characterized in that: The steps include: S1: wet-grinding a mixture of a sodium source, an iron source, a phosphorus source, gelatin and carbon nanotubes to obtain a slurry; S2: spray drying the slurry to obtain a precursor powder; S3: The precursor powder obtained in step S2 is subjected to a one-step calcination treatment in an oxygen-free environment to obtain a sodium iron phosphate pyrophosphate positive electrode material having a cactus-shaped surface coated with nitrogen-doped carbon material.
2. The method for preparing the cactus-shaped sodium ion battery positive electrode material according to claim 1, characterized in that: In step S1, the molar ratio of sodium element, iron element and phosphorus element in the sodium source, iron source and phosphorus source is 4:(2.8-3):4; The carbon element in the gelatin accounts for 1-5% of the total mass of the mixture of the sodium source, the iron source, the phosphorus source, the gelatin and the carbon nanotubes; Carbon nanotubes make up 5-15% of the gelatin mass.
3. The method for preparing the cactus-shaped sodium ion battery positive electrode material according to claim 1, characterized in that: In step S1, the sodium source is one or more of sodium carbonate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium oxalate and sodium pyrophosphate; The iron source is one or more of ferrous phosphate, ferrous citrate, ferrous oxalate, ferrous acetylacetonate, ferrous nitrate, ferric chloride and ferrous sulfate; The phosphorus source is one or more of phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ferric phosphate, ferric pyrophosphate and sodium dihydrogen phosphate.
4. The method for preparing the cactus-shaped sodium ion battery positive electrode material according to claim 1, characterized in that: In step S1, a sodium source, an iron source, a phosphorus source, gelatin and carbon nanotubes are mixed, water is added to obtain a mixed material, and then wet-milling is performed; Among them, the rotation speed of wet grinding is 2000-3000r / min, the flow rate of the mixed material through the wet grinding equipment during wet grinding is 50-100L / h, the duration of wet grinding is 0.5-10h, the particle size of the grinding medium used in wet grinding is 0.03-0.3mm, and the grinding medium occupies 70-85% of the volume of the grinding chamber.
5. The method for preparing the cactus-shaped sodium ion battery positive electrode material according to claim 1, characterized in that: The slurry obtained in step S1 has a solid content of 15-40 wt % and a particle size of the solid particles of 50-200 nm.
6. The method for preparing the cactus-shaped sodium ion battery positive electrode material according to claim 1, characterized in that: In step S2, the feed rate of spray drying is 60-90 mL / min, the pressure of the spray gun is 0.2-0.4 MPa, the feed temperature is 190-240°C, and the discharge temperature is 80-130°C.
7. The method for preparing the cactus-shaped sodium ion battery positive electrode material according to claim 1, characterized in that: In step S3, the precursor powder obtained in step S2 is subjected to a one-step calcination treatment in a mixed atmosphere of nitrogen and ammonia to obtain a sodium iron phosphate pyrophosphate positive electrode material having a cactus-shaped surface coated with a nitrogen-doped carbon material; In the mixed atmosphere, ammonia accounts for 10-20% by volume.
8. The method for preparing the cactus-shaped sodium ion battery positive electrode material according to claim 1, characterized in that: In step S3, the precursor powder is heated to 400-600°C at a heating rate of 2-8°C / min, calcined for 5-16h, and then cooled.
9. The method for preparing the cactus-shaped sodium ion battery positive electrode material according to claim 8, characterized in that: In step S3, the cooling time is 10-60 minutes.
10. The method for preparing the cactus-shaped sodium ion battery positive electrode material according to claim 1, characterized in that: In step S3, the structure of the sodium iron phosphate pyrophosphate positive electrode material with a cactus-shaped surface coated with nitrogen-doped carbon material is Na4Fe x (PO4)2P2O7@CN, 2.8<x≤3.
Citation Information
Patent Citations
Preparation method of composite phosphoric acid and ferric sodium pyrophosphate polyanionic positive electrode material and application of composite phosphoric acid and ferric sodium pyrophosphate polyanionic positive electrode material in sodium-ion battery
CN116002650A
High-entropy ferric sodium pyrophosphate sodium ion battery positive electrode material and preparation method thereof
CN116404154A
Sodium ferric phosphate pyrophosphate carbon composite positive electrode material as well as preparation method and application thereof
CN117374257A
Process for preparing ferric sodium pyrophosphate positive electrode material by recovering ferrophosphorus slag
CN117383534A
Sodium-ion battery positive active material, preparation method thereof and sodium-ion battery
CN118039843A